Choice of point of Care diagnostic device in anemia prevalence surveys: policy-level Implications in monitoring progress and guiding further action. - Mahajan, Preetam B; A, Newtonraj; Bazroy, Joy; Sinha, Anju; Kapil, Umesh; Purty, Anil (Indian Journal of Community Health, 2018)
Anemia is highly prevalent disease of global concern. Childhood anemia can result in irreversible damage to brain and affect cognitive, intellectual, and pyscho-motor development. In pregnant women, it is a significant contributor to adverse maternal outcome (1–4). In 2011, alone it was responsible for loss of 42 million Disability adjusted life years and among the top three causes of disability worldwide (5). In an attempt to address this huge public health problem, guidelines have been issued by various leading international organizations and targets have been set to monitor progress towards its control. One such indicator is 50% reduction of anemia in women in reproductive age group (WRA) between 2011 and 2025 (6). This makes it necessary to carry out huge population-based anemia prevalence surveys repeatedly, to measure the progress and guide policy makers in carrying out specific interventions needed to reduce its prevalence.